Bioactive compounds and antioxidant activity of Annona muricata L. fruits located in Manabí, Ecuador - Párraga, Cecilia; Rincón-Acosta, Fernando; Barre-Zambrano, Roy; Vera-Cedeño, Jhon; Vargas, Plinio; Mendoza , Freddy (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2024)
The mesoendocarp of Annona muricata L. (Annonaceae) has essential minerals, ascorbic acid, dietary fiber, polyphenols, and acetogenins in its composition, which evidences the nutraceutical benefits of this fruit tree. This study aimed to determine the bioactive compounds and antioxidant activity of A. muricata fruits located in Manabí, Ecuador. The content of vitamin C, dietary fiber, minerals, polyphenols, flavonoids, antioxidant activity, and the presence of acetogenins were determined. It was observed that the minerals potassium, calcium, sodium, zinc, magnesium, and iron are the major components present in soursop pulp ash. Likewise, relevant content of vitamin C (26.64 mg AA.100 g-1 pulp), total polyphenols (398.79 mg EAG.100 g-1 pulp), flavonoids (192.20 mg EQ.100 g-1 pulp), and high antioxidant activity (318.90 mmol equivalents of trolox.100 g-1 pulp) were evidenced in the fruits of A. muricata. The ethanolic extracts obtained from the fruit when applying the Kedde test, presented a pink ring, which is an unequivocal indicator of the presence of acetogenins, which have a proven antineoplasic effect. The mesoendocarp of A. muricata located in Manabí, Ecuador has an important content of bioactive compounds: essential minerals (K, Ca, Zn, Mg), vitamin C, polyphenols, presence of acetogenins and high antioxidant activity, properties that reduce the risk of degenerative diseases and cellular aging. Therefore, its consumption is recommended in the daily diet as fresh and processed fruit because it constitutes a valuable nutritional and therapeutic alternative.